2001
DOI: 10.1176/appi.ps.52.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Mental Illness and Child Maltreatment Risk Among Mothers With Major Psychiatric Disorders

Abstract: Insight into mental illness may function as a protective factor that influences the risk of child maltreatment in mothers with mental illness. Measures of insight could be usefully incorporated into comprehensive parenting assessments for mothers with psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 34 publications
0
47
0
1
Order By: Relevance
“…A recent study (Mullick, Miller, & Jacobsen, 2000) found that the level of insight a mother has into her mental illness is significantly negatively correlated to her risk of abusing her children. Insight into mental illness was also significantly positively correlated with ratings of maternal sensitivity.…”
Section: Child Welfarementioning
confidence: 99%
“…A recent study (Mullick, Miller, & Jacobsen, 2000) found that the level of insight a mother has into her mental illness is significantly negatively correlated to her risk of abusing her children. Insight into mental illness was also significantly positively correlated with ratings of maternal sensitivity.…”
Section: Child Welfarementioning
confidence: 99%
“…Maternal mental distress can be associated with increased rate of stillbirth, pre-term birth, post-natal specialist care for the baby, and low birth-weight babies (Ding et al, 2014, Kim et al, 2013. Untreated mental health 4 problems in pregnancy are also associated with poorer long-term outcomes for children, including decreased emotional and cognitive development, and difficulties developing and maintaining relationships and attachment (Fendrich et al, 1990, Goodman and Brumley 1990, Hammen et al, 1990, Kelly et al, 1999, Mullick et al, 2001. While perinatal mental health issues are a major health concern, early detection, prompt intervention, and support can improve maternal and infant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The child welfare field continues to distinguish between situations where a child is at risk of maltreatment and situations where incidents of maltreatment have occurred (Berger and Brooks-Gunn 2005;Hamilton-Giachritsis and Browne 2005;Jaudes and Mackey-Bilaver 2008;Mullick et al 2001;Portwood 1999;Scannapieco and Connell Carrick 2003). In practice, child welfare workers investigate and intervene in many situations in which children have not yet been physically harmed but have been maltreated, and situations where children live in environments and with caregivers whose risk factors increase the likelihood that they will experience maltreatment (Bala 2004;Trocmé et al 2010a).…”
mentioning
confidence: 99%